Variations in the 6.2 μm emission profile in starburst-dominated galaxies: a signature of polycyclic aromatic nitrogen heterocycles (PANHs)?. Issue 3 (4th January 2018) - Canelo, Carla M; Friaça, Amâncio C S; Sales, Dinalva A; Pastoriza, Miriani G; Ruschel-Dutra, Daniel
Abstract: Analyses of the polycyclic aromatic hydrocarbon (PAH) feature profiles, especially the 6.2 μm feature, could indicate the presence of nitrogen incorporated in their aromatic rings. In this work, 155 predominantly starburst-dominated galaxies (including H ii regions and Seyferts, for example), extracted from the Spitzer /Infrared Spectrograph ATLAS project, have their 6.2 μm profiles fitted allowing their separation into the Peeters' A, B, and C classes. 67 per cent of these galaxies were classified as class A, 31 per cent were as class B, and 2 per cent as class C. Currently, class A sources, corresponding to a central wavelength near 6.22 μm, seem only to be explained by polycyclic aromatic nitrogen heterocycles (PANHs), whereas class B may represent a mix between PAHs and PANHs emissions or different PANH structures or ionization states. Therefore, these spectra suggest a significant presence of PANHs in the interstellar medium (ISM) of these galaxies that could be related to their starburst-dominated emission. These results also suggest that PANHs constitute another reservoir of nitrogen in the Universe, in addition to the nitrogen in the gas phase and ices of the ISM.